2016
DOI: 10.1108/gm-04-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Representing women? Leadership roles and women in Canadian broadcast news

Abstract: Purpose The purpose of this paper is to examine the representation of women in Canadian broadcast news coverage, exploring the notion of substantive representation as it relates to gender, leadership and framing. Design/methodology/approach Using computer-aided text analysis software, the authors analyzed the frequency of women appearing in on-air roles, the way in which they are framed, as well as technical and expressive details, such as how they are featured. In total, the authors analyzed representation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Past research has discovered males to be the most prominent gender shown as news talent in television news (Cann & Mohr, 2001;"New Research," 2014;Cukier et al, 2016). However, research from 2010 in the Northeast region of the United States found no significant difference between males and females as news talent (Desmond & Danilewicz).…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Past research has discovered males to be the most prominent gender shown as news talent in television news (Cann & Mohr, 2001;"New Research," 2014;Cukier et al, 2016). However, research from 2010 in the Northeast region of the United States found no significant difference between males and females as news talent (Desmond & Danilewicz).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…However, Armstrong et al, (2006) discovered male and female news talent, anchors and reporters, were displayed virtually equally in local newscasts in Wisconsin, however, females were not as apparent in network television newscasts. According to (Irvin, 2013;"New Research," 2014;Cukier et al, 2016) males are still the common face on the television news screen as anchors and reporters.…”
Section: Gender Presentationsmentioning
confidence: 99%
See 3 more Smart Citations